Is it worthwhile rethinking the positive experience of the last 50 years of using chondroitin sulfates against atherosclerosis? - A. M. Lila; I. Yu. Torshin; O. A. Gromova (Фармакоэкономика, 2020)
Chondroitin sulfate (CS) and glucosamine sulfate (GS) are used in the treatment of osteoarthritis and exhibit a pronounced anti-inflammatory effect. CS/GS inhibit the NF-kB signaling cascade, which realizes the biological effects of tumor necrosis factor (TNFa). Excessive activity of NF-kB also stimulates the development of atherosclerosis. The results of experimental and clinical studies show that inhibition of NF-kB by CS/GS will inhibit the formation and growth of atherosclerotic plaques also reducing levels of other markers of inflammation.